KONSEP GENDER DAN PENGARUSUTAMAAN GENDER - Sudarta, Wayan (Jurnal Studi Jender SRIKANDI; Vol. 3, No. 1 Januari 2004)
This article aims to give the understanding about gender and its mainstreams and also present some terms related to gender. Understanding and applying the concept of gender is to realize equivalence and justice of gender in our life and development. The mainstreams of gender are the strategies to gain the equivalence of harmonious between men with women. Due to accelerate the understanding and applying the concept of gender and its mainstream in various life area and development, hence some terms of gender require comprehending.
Keywords: gender, pengarusutamaan gender